2006
DOI: 10.1103/physrevlett.97.163901
|View full text |Cite
|
Sign up to set email alerts
|

Heterodyne Mixing of Laser Fields for Temporal Gating of High-Order Harmonic Generation

Abstract: The concept of heterodyne mixing of laser fields is theoretically applied to the process of high-harmonic generation to enhance and modulate the kinetic energy of the active electron on subcycle time scales. A very small amount of intensity in the heterodyne field creates a significant modification of the electron kinetic energy, due to its amplification by the strong fundamental field in the kinetic-energy term, in which the heterodyne mixing occurs. Quantum calculations are carried out to verify the predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
78
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(81 citation statements)
references
References 17 publications
2
78
0
1
Order By: Relevance
“…Our work builds on a long history of experiments on using multiple color fields to produce high harmonics [10][11][12][13][14][15][16][17][18]. Early experiments confirmed that energy, momentum, and parity are preserved when high harmonics are generated in two-color fields [10].…”
mentioning
confidence: 99%
“…Our work builds on a long history of experiments on using multiple color fields to produce high harmonics [10][11][12][13][14][15][16][17][18]. Early experiments confirmed that energy, momentum, and parity are preserved when high harmonics are generated in two-color fields [10].…”
mentioning
confidence: 99%
“…A well-known example of a heterodyne detector is the radio. Heterodyne detection is also widely used in optics, in quantum devices, in the detection of nuclear magnetic resonance, in microwave detection, in scanning tunnelling spectroscopy and even in the search for gravitational waves [1][2][3][4][5][6][7] .…”
mentioning
confidence: 99%
“…This is much more sensitive than the signal field alone. Heterodyne techniques have been used in the field of optics and recently it was pointed out by Pfeifer et al [19] that the two-color scheme used for creating attosecond pulses is a virtue of the heterodyne method. According to the theory of harmonic heterodyne mixing, the characteristics of the signal field can be efficiently enlarged by the local oscillator.…”
Section: Introductionmentioning
confidence: 99%
“…Heterodyne theory has been used in various areas of science and engineering. The theory is based on superposing a weak signal pulse onto a strong coherent reference pulse [19]. The intensity of the combined field is proportional to the square of the total electric field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation